2013
DOI: 10.1158/1535-7163.mct-12-0782
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress and the Unfolded Protein Response: Targeting the Achilles Heel of Multiple Myeloma

Abstract: Multiple myeloma is characterized by the malignant proliferating antibody-producing plasma cells in the bone marrow. Despite recent advances in therapy that improve the survival of patients, multiple myeloma remains incurable and therapy resistance is the major factor causing lethality. Clearly, more effective treatments are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
140
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(143 citation statements)
references
References 74 publications
(97 reference statements)
0
140
0
3
Order By: Relevance
“…The IRE1α/XBP1 pathway is often activated in cancers and has recently emerged as a potential molecular target for anticancer therapy (1,5,(39)(40)(41)(42)(43), especially for multiple myeloma, which is characterized by malignant plasma cells producing a high amount of immunoglobulin (26,42,44,45). These previous studies showed that the pharmacological inhibition of IRE1α endonuclease significantly suppressed myeloma tumor growth in a model of human malignant myeloma xenografts, corroborating the idea that the IRE1α/XBP1 pathway may serve as a promising molecular target.…”
Section: Discussionmentioning
confidence: 99%
“…The IRE1α/XBP1 pathway is often activated in cancers and has recently emerged as a potential molecular target for anticancer therapy (1,5,(39)(40)(41)(42)(43), especially for multiple myeloma, which is characterized by malignant plasma cells producing a high amount of immunoglobulin (26,42,44,45). These previous studies showed that the pharmacological inhibition of IRE1α endonuclease significantly suppressed myeloma tumor growth in a model of human malignant myeloma xenografts, corroborating the idea that the IRE1α/XBP1 pathway may serve as a promising molecular target.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons were made to multiple myeloma, known to be associated with UPR activation. 39 Overall, PERK and XBP1 were widely detected in LN samples; 11 of 11 and 10 of 11 samples were positive for PERK and XBP1 expression, respectively. Similar to myeloma samples, PERK immunostaining was largely extranuclear, consistent with endoplasmic reticulum localization.…”
mentioning
confidence: 83%
“…Defense against stress misfolded proteins exert on the endoplasmic reticulum (ER) has been identified as Achilles heel of multiple myeloma (3). Proteins destined for secretion enter the ER in an incompletely folded state and factors commonly found in cancer, like augmented protein synthesis, nutrient deficiency, and hypoxia increase them or impair their folding exerting ER stress (4).…”
Section: Introductionmentioning
confidence: 99%